Endovascular treatment of aneurysms of the paraophthalmic segment of the internal carotid artery: Current status - Wang, Yiheng; Yu, Jinlu (Frontiers in Neurology, 2022)
Aneurysms arising from the paraophthalmic segment of the internal carotid artery (ICA) represent approximately 5%-10% of intradural aneurysms. Because of the complex nearby structures and a higher rate of visual deficits, surgical clipping for these aneurysms poses challenges. Due to the advent of endovascular treatment (EVT) techniques and devices, specifically flow diverting stents (FDSs), EVT has become the first-line treatment for these aneurysms. However, EVT may be challenging. Therefore, it was necessary to conduct a literature review and recount our experience. In this review, we discussed the following issues: anatomy of the paraophthalmic segment, classification of the aneurysms, EVT principle and techniques and prognosis and complications. EVT techniques for aneurysms of the paraophthalmic segment include coil embolization, FDSs, covered stents and Woven EndoBridge devices. Currently, coiling embolization remains the first choice for ruptured aneurysms, especially to avoid long-term antiplatelet therapy for young patients. For unruptured aneurysms, due to the excessive use of antiplatelet therapy, it was not the time for aneurysms that were easy to be coiled to make way for FDS. The FDS was appropriate for uncoilable or failed aneurysms. Other devices cannot act as the first choice but as useful auxiliary tools. Both coiling embolization and FDS deployment can result in a good prognosis for aneurysms of the paraophthalmic segment. The overall complication rate was low. Therefore, current EVT techniques offer promising treatments for aneurysms of the paraophthalmic segment of the ICA.